Atributos físico-hídricos do solo em área de plantio direto com e sem terraços agrícolas - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
Studies related to factors that directly affect hydrological processes are important for soil and water conservation and for the implementation of new agricultural production models. The objective of this work was to evaluate the physical-hydric attributes of the soil in a no-tillage area on a megaplot scale, with and without agricultural terraces in the Campos Gerais region of Paraná. State of Ponta Grossa (UEPG), on a slope where the soil is classified as a typical Dystrophic Red-Yellow Latosol. Saturated hydraulic conductivity was determined with modified Philip-Dunne permeameters, soil water retention curves were determined at matrix potentials -1, -3, -6, -10, -30, -50, -75, - 1000 and -1500 kPa, by van Genuchten. The data obtained were initially submitted to descriptive statistics, analysis of extreme values using the box-plot and Grubbs method (p>0.05), residual normality test using the Shapiro-Wilk method (p>0.05), and were transformed using the Box-Cox test or √(x+1), and confidence intervals were performed using the Student t test. Through the CRAs, it was found that the areas with and without agricultural terraces presented different behaviors for the lower tensions, in the different positions of the slope in the mega-plots. Higher values of volumetric humidity in the tensions between 1.0 and 10 hPa Saturated hydraulic conductivity reduced 55.7% from the first to the second year in the megaplot with terrace, and 17.8% from the first to the second year for the megaplot without agricultural terraces, in which the greatest reduction occurred in the MPC. Through the CRAs parameters, it was found that the alpha parameter (α) showed a high change between the first and second year of collection, indicating a high change in the porous system of the soil.
Keywords: Condutividade hidráulica saturada; Método Philip-dunne modificado; Infiltração de água no solo; Curva de retenção de água no solo; Hidrologia de superfície; Saturated hydraulic conductivity; Modified Philip-dunne method; Soil water infiltration; Soil water retention curve; Surface hydrology; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA